2007
DOI: 10.1111/j.1469-1809.2007.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in interleukin 6 (IL‐6) and IL6 receptor genes in spontaneous preterm birth and effects on amniotic fluid protein levels

Abstract: SummaryPreterm birth (PTB) is a significant neonatal health problem that is more common in African-Americans (AA) than in European-Americans (EA). Part of this disparity is likely to result from the differing genetic architectures of EA and AA. To begin assessing the role of these differences, patterns of genetic variation in two previously proposed candidate genes, encoding interleukin 6 (IL6) and its receptor (IL6R), were analyzed in mothers and fetuses from 496 EA birth-events (149 cases and 347 controls) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 36 publications
4
49
1
2
Order By: Relevance
“…In agreement with previous studies in the general population, our data have suggested racial differences on IL-6 levels. 4,5,28 Consistent with prior reports, differences in IL-6 production were evident between non-Hispanic Caucasians, Hispanics, and African Americans, with African Americans exhibiting the lowest IL-6 levels. 29 More critically, however, our study extends earlier findings by showing, for the first time, that using mentholated cigarettes may impose additional burdens on the body's regulation of inflammatory response among African Americans and Hispanics living with HIV.…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with previous studies in the general population, our data have suggested racial differences on IL-6 levels. 4,5,28 Consistent with prior reports, differences in IL-6 production were evident between non-Hispanic Caucasians, Hispanics, and African Americans, with African Americans exhibiting the lowest IL-6 levels. 29 More critically, however, our study extends earlier findings by showing, for the first time, that using mentholated cigarettes may impose additional burdens on the body's regulation of inflammatory response among African Americans and Hispanics living with HIV.…”
Section: Discussionsupporting
confidence: 78%
“…99,100 In fact, the concentrations of interleukins-6 and -8 in the amniotic fluid were similar between preterm and term samples in African Americans, whereas they were significantly higher in European American cases compared with European American controls. 99,101 If these findings are confirmed, it would indicate that predictive biomarkers in this condition perform differently across ethnic populations and/or geographical locations. Fourth, novel biomarkers could have different predictive ability depending upon the gestational age at birth.…”
Section: Discussionmentioning
confidence: 98%
“…[34][35][36] Gender differences in IL-6 production have been reported in previous studies; 37,38 therefore, IL-6 or IL-6R polymorphisms that modify IL-6 levels might potentially contribute to sex disparity. For the IL-6R polymorphisms, some studies have focused on women (studying IL-6 levels, CRP levels, bone mineral density, obesity, hyperandrogenism, preterm birth, type 2 diabetes and melanoma), 7,29,[39][40][41][42][43][44] and one on men (studying obesity). 45 Most analyses of IL-6R gene polymorphisms have not investigated (or at least have not reported) gender differences.…”
Section: Discussionmentioning
confidence: 99%